2019
DOI: 10.3390/w11010146
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Features of Flow through Local Non-Submerged Rigid Vegetation in the Y-Shaped Confluence Channel

Abstract: A laboratory measurement with acoustic Doppler velocimeter (ADV) was used to investigate the flow through a Y-shaped confluence channel partially covered with rigid vegetation on its inner bank. In this study, the flow velocities in cases with and without vegetation were measured by the ADV in a Y-shaped confluence channel. The results clearly showed that the existence of non-submerged rigid plants has changed the internal flow structure. The velocity in the non-vegetated area is greater than in the vegetated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Liu and Shan [22] used an analytical model to predict longitudinal profile of depth averaged streamwise velocity for simulated emergent cylindrical vegetation and used an experimental setup to validate the proposed model for short and long arrays of vegetation. Tong et al [23] investigated the effect of emergent rigid vegetation in a y shaped confluence channel and concluded that non submerged vegetation is responsible for changing the flow structure. Due to the vegetation, middle of the non-vegetated area in the vicinity of tributaries showed existence of high velocity region, and the disappearance of the secondary flow.…”
Section: Vertical Structurementioning
confidence: 99%
“…Liu and Shan [22] used an analytical model to predict longitudinal profile of depth averaged streamwise velocity for simulated emergent cylindrical vegetation and used an experimental setup to validate the proposed model for short and long arrays of vegetation. Tong et al [23] investigated the effect of emergent rigid vegetation in a y shaped confluence channel and concluded that non submerged vegetation is responsible for changing the flow structure. Due to the vegetation, middle of the non-vegetated area in the vicinity of tributaries showed existence of high velocity region, and the disappearance of the secondary flow.…”
Section: Vertical Structurementioning
confidence: 99%
“…Yet, the shear layer dynamics may be influenced by the presence of vegetation because plants may affect the internal flow structure at a confluence especially in the secondary flow structure (Tong et al, 2019). As a result, our analysis shows that the vegetation may be the key driver of the junction hydrodynamics, with respect to other hydraulic and morphological features (e.g., discharge ratio, junction angle).…”
Section: River Confluences Morphodynamics In Presence Of Riparian Vegetationmentioning
confidence: 79%
“…The flow patterns at confluences influence the contaminant transport and affect the bed morphology in river networks (Kilic & Aral, 2009). Many studies have been conducted to explore the hydrodynamic features in river confluences (Boyer et al, 2006; Liu et al, 2019; Qing‐Yuan et al, 2009; Tong et al, 2019). Taylor (1944) was the first to study the hydraulic characteristics in open‐channel confluences through flume experiments.…”
Section: Introductionmentioning
confidence: 99%